Answers

2014-07-13T12:52:01+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
So AC = CB
AD = AB + BD
AD + BD = AB + 2BD
AD + BD = AC + BD + CB + BD
AD + BD = CB  + BD + CB + BD   [SINCE AC = CB]
AD + BD = CD + CD
AD + BD = 2CD    HENCE PROVED

0
  • Brainly User
2014-07-13T12:56:57+05:30
Sice C bisects
so AC = CB
AD = AB + BD
AD + BD = AB + 2BD
AD + BD = AC + BD + CB + BD
AD + BD = CB  + BD + CB + BD   (since AC = CB)
AD + BD = CD + CD
AD + BD = 2CD   
so proved

0